Menumbuhkembangkan Keterampilan 4C Melalui Problem Based Learning (PBL) Terintegrasi Role Playing dan Game Quizziz - Nafiah, Tri (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2024)
This research discusses the use of the Problem Based Learning (PBL) learning model which is integrated with the Role Playing method and the Quizziz game platform in improving 4C skills (Critical Thinking, Communication, Collaboration, and Creativity) in 4th grade elementary school students in understanding the rights and obligations of students. Pancasila Education lessons. In the 21st century era of education, the need to develop these essential skills is crucial to prepare students to face an ever-changing environment. PBL, with a focus on solving problems relevant to everyday life, is integrated with role playing and Quizziz games as an innovative solution in learning. The research method used is descriptive qualitative with a focus on an integrated learning approach. The research was conducted at SD Negeri Semarangan 1 involving 25 grade 4 students as research subjects. Data was collected through documentation and observation techniques. The results of the research show that through structured learning steps, such as student orientation towards problems, student organization for learning, individual and group investigation guidance, development and presentation of work results, as well as analysis and evaluation of the problem solving process, 4C skills can grow and develop in student. Students engage in collaboration, communication, creativity, and critical thinking while undergoing these learning stages. Keywords: PBL, role playing, quizziz.